THE INFLUENCE OF HEALTH EDUCATION THROUGH LEAFLETS AND VIDEO MEDIA ON KNOWLEDGE ABOUT THE DANGERS OF SMOKING IN STUDENTS OF JUNIOR HIGH SCHOOL 1 PETERONGAN - Prawito Prawito; Djihan Ibura; Eliza Zihni Zatihulwani (Literasi Kesehatan Husada)
Background: Smoking is an unhealthy habit that can cause various diseases. Health education is essential to improve understanding of the dangers of smoking.